Testing of a 3D-Printed Solar Micro-Reactor for Hydrogen Production via Natural Gas Reforming. (November 2019) - Camus, Paul; Dufault, J-F.; Mehanovic, D.; Braidy, N.; Fréchette, L. G.; Picard, M.
Abstract: This paper presents the design, fabrication, and successful real-condition testing of a solar micro-reactor for hydrogen synthesis via steam methane reforming (SMR). This micro-reactor integrates all the sub-processes necessary for SMR in a network of small three-dimensional channels, making it well-suited for implementation on the commercially available parabolic trough solar concentrators. Additive manufacturing was used to create an operational prototype of this micro-reactor. The prototype was integrated to a parabolic mirror for solar concentration, and tested in real conditions. Complete methane conversion to syngas was obtained with an absorbed solar radiation equivalent to 240 suns, which demonstrates the feasibility of solar SMR at moderate solar concentration.